Polar and semipolar (112‾2) InAlN layers grown on AlN templates using MOVPE. Issue 1 (12th November 2015) - Dinh, Duc V.; Li, Haoning; Parbrook, Peter J.
Abstract: We report on metalorganic vapor phase epitaxial growth of InAlN layers on (0001) and (11 2 ‾ 2) AlN templates at different temperatures (725–800 °C). The indium content (8.0–15.2%) of the (11 2 ‾ 2) InAlN layers was found to be lower compared to that for the (0001) layers (9.0–23.0%). The higher indium content of the (0001) layers was attributed to a high density of small hillocks and a larger degree of relaxation. The small hillocks on the (0001) layer surface acted as quantum‐dot‐like structures that caused a stronger emission at longer wavelength compared to weaker emission at shorter wavelength from a "bulk" layer underneath. A large Stokes‐shift of about 300 and 480 meV was observed for the (0001) and ( 11 ̅ 2 2 ) layers, respectively. The larger shift of the (11 2 ‾ 2) layers was attributed to a higher degree of localization. The larger degree of localization and higher unintentional oxygen incorporation enhanced the luminescence intensity of the (11 2 ‾ 2) layers compared to that for the (0001) layers.